Application of E-Government to Financial Accountability in the Surabaya City - Puspitarini, Ririn (Fakultas Ekonomi Universitas Samudra, 2023)
This research aims to explain specifically the implementation of e-government used by the Surabaya City government office regarding regional financial accountability. Financial accountability in the Surabaya City government is not optimal due to one of its elements, namely the implementation of the publication of financial reports has not been carried out through the implementation of e-government. This situation also results in the objectives of e-government implementation not running well. This phenomenological qualitative research is to reveal problems in regional financial management in an accountable manner. The approach used is a case study. The results obtained show that the element of accountability is already accountable. However, the accountability carried out in the implementation of e-government is only limited to planning and implementation. Publication of financial reports has not been carried out because it is still limited by policies and regulations.